2017
DOI: 10.25275/apjcectv3i2edu2
|View full text |Cite
|
Sign up to set email alerts
|

The New General Self-Efficacy Scale: A Matter of Language

Abstract: General Self-Efficacy (GSE) scales are used to measure the extent to which individuals possess a general sense of mastery that is not tied to a specific situation or behavior. The present study assesses whether the language in which a GSE scale is presented yields different responses in Arabic-English bilingual female students and whether differences can be traced to emotional reactions triggered by cultural norms dictating modesty in attitudes and behavioral expression. Female students residing in the Eastern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…None of the studies reported test-retest reliability for the African language versions of the instruments. There are also recent indications of differences in obtained scores when the same sample of participants complete both the English language and native language versions of a questionnaire, especially when emotional responses and cultural orientations are triggered [56] . The present researchers did not identify any sample in the translated measures where both English language and African language versions were tested in the same study.…”
Section: Resultsmentioning
confidence: 99%
“…None of the studies reported test-retest reliability for the African language versions of the instruments. There are also recent indications of differences in obtained scores when the same sample of participants complete both the English language and native language versions of a questionnaire, especially when emotional responses and cultural orientations are triggered [56] . The present researchers did not identify any sample in the translated measures where both English language and African language versions were tested in the same study.…”
Section: Resultsmentioning
confidence: 99%